Pengaruh Internal Auditor dan Internal Control terhadap Pencapaian Prinsip Good University Governance di Universitas Nusa Nipa - Ellygius Mario Pablo Tani; Yosefina Andia Dekrita; Paulus Libu Lamawitak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aimed to determine the influence of Internal Auditors and Internal Control on achieving Good University Governance at Nusa Nipa University. The research employed an associative approach with a causal relationship and a quantitative method. The sampling technique used was Quota Sampling, where the sample was determined based on a predetermined quota. Data collection was carried out through the distribution of questionnaires to 45 respondents. Data analysis was conducted using multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) software. The results of the study indicated that the significance value (sig) for the Internal Auditor variable (X1) was 0.000, which was less than the significance level of 0.05, and the Internal Control variable (X2) also had a sig value of 0.000, which was below the significance level of 0.05. The F-test results showed that the F value was 22.831 with a significance level of 0.000. Based on the F-test results, it was found that the independent variables collectively had a significant effect on the dependent variable, namely the achievement of Good University Governance. Thus, it was concluded that Internal Auditors and Internal Control significantly influenced the achievement of Good University Governance at Nusa Nipa University.